A novel framework for analysing stakeholder interest in healthy foods: A case study on iodine biofortification. Issue 2 (3rd March 2016) - Mogendi, Joseph Birundu; De Steur, Hans; Gellynck, Xavier; Makokha, Anselimo
ABSTRACT: Despite the availability of novel strategies to prevent micronutrient malnutrition, such as biofortification, limited understanding of stakeholders often hampers their success. We build upon the existing literature on protection motivations (PMT) and technology acceptance (TAM) to develop an integrated PMTAM model for analyzing stakeholders' reactions, on both the supply and demand sides. Regarding the latter, the case of the iodine biofortified food chain is used to evaluate African households' interest. All model constructs, and threat appraisal in particular, are decisive in determining the uptake of biofortification, while also social demographics and own nutrition status play an important role.